Comparative Analysis of Right Ventricle Fluid Dynamics - Collia, Dario; Zovatto, Luigino; Tonti, Giovanni; Pedrizzetti, Gianni (Frontiers in Bioengineering and Biotechnology, 2021)
The right and left sides of the human heart operate with a common timing and pump the same amount of blood. Therefore, the right ventricle (RV) presents a function that is comparable to the left ventricle (LV) in terms of flow generation; nevertheless, the RV operates against a much lower arterial pressure (afterload) and requires a lower muscular strength. This study compares the fluid dynamics of the normal right and left ventricles, to better understand the role of the RV streamlined geometry and provide some physics-based ground for the construction of clinical indicators for the right side. The analysis is performed by image-based direct numerical simulation, using the immersed boundary technique including the simplified models of tricuspid and mitral valves. Results demonstrated that the vortex formation process during early diastole is similar in the two ventricles, then the RV vorticity rapidly dissipates in the subvalvular region while the LV sustains a weak circulatory pattern at the center of the chamber. Afterwards, during the systolic contraction, the RV geometry allows an efficient transfer of mechanical work to the propelled blood; differently from the LV, this work is non negligible in the global energetic balance. The varying behavior of the RV, from reservoir to conduct, during the different phases of the heartbeat is briefly discussed in conjunction to the development of possible dysfunctions.